2021
DOI: 10.1086/709277
|View full text |Cite
|
Sign up to set email alerts
|

How Do Employers Use Compensation History? Evidence from a Field Experiment

Abstract: We report the results of a field experiment in which treated employers could not observe the compensation history of their job applicants. Treated employers responded by evaluating more applicants, and evaluating those applicants more intensively. They also responded by changing what kind of workers they evaluated: treated employers evaluated workers with 7% lower past average wages and hired workers with 16% lower past average wages. Conditional upon bargaining, workers hired by treated employers struck bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…Yet the paucity of studies that document the practice in context find extremely low base rates. For example, just 14% of successful candidates reported negotiating their final salary in our experiment, which is remarkably consistent with the 14% rate reported by Leibbrandt and List (2015) and the 11% rate reported by Barach and Horton (2021).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Yet the paucity of studies that document the practice in context find extremely low base rates. For example, just 14% of successful candidates reported negotiating their final salary in our experiment, which is remarkably consistent with the 14% rate reported by Leibbrandt and List (2015) and the 11% rate reported by Barach and Horton (2021).…”
Section: Discussionsupporting
confidence: 89%
“…This motivates the need for an experimental assessment, conducted with sufficient external validity to draw 2 See https://www.hrdive.com/news/california-bans-the-box-outlaws-salary-history-questions/507340/ credible conclusions. Barach and Horton (2021) provide the only such example to date. They found, in a study of freelancers, that workers whose past earnings were obscured received higher wages-conditional on negotiating, which occurred in 11% of the filled roles in their sample.…”
mentioning
confidence: 99%
“…A series of empirical papers study salary history bans using panel methods and a variety of observational data sets (Bessen et al, 2020;Davis et al, 2020;Hansen and McNichols, 2020;Mask, 2020;Sinha, 2019;Sran et al, 2020). A few other researchers have examined the effect of salary disclosures and salary history bans using experiments in online markets (Barach and Horton, 2021), laboratory settings (Khanna, 2020), or in real-life educational institutions (Sherman et al, 2019).…”
Section: Salary History Bansmentioning
confidence: 99%
“…Survey evidence suggests that up to 43% of job applicants are asked about salary history during job search (Hall and Krueger, 2012;PayScale, 2017;Barach and Horton, 2021;Agan et al, 2020;Cowgill et al, 2021). In our own survey, the most common method of inquiring about salary history was on job application forms (in writing).…”
Section: Background: Salary History Questionsmentioning
confidence: 99%
“…One study has found that policies which limit employer access to wage history benefit those with relatively lower wages as employers without information on wage history arranged more face-to-face interviews and asked more questions during interviews than those employers who had wage information (Barach & Horton, 2017). These outcomes allow job applicants a greater opportunity to present their potential value and contributions to employers.…”
Section: Are Salary Inquiry Bans Working Thus Far?mentioning
confidence: 99%